Assimilate Partitioning and Agronomic Performance of Floating Rice in Flood-Prone Ecosystems of Indonesia - Nasrudin, Nasrudin; Dwiyani, Monita; Mardiansyah, Dian; Taufik, Riad (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2025)
Rice cultivation in flood-prone areas often results in a decrease in yield and crop failure. The Floating Rice Field (FRF) method is a strategy to increase plant resilience while improving rice production in flood-prone areas. The choice of the right seedling makes it easier for plants to adapt to the FRF method, improving physiological traits, growth, and yield. The aim of this research was to investigate the effects of seedling age on the agronomic performance and assimilate partitioning of rice planted using the FRF method in the flood-prone areas. A field experiment was conducted in Pangandaran, Indonesia. The study was arranged as a 2x2 factorial randomized complete block design with seedling age (14 DAS and 21 DAS) as the first factor and rice variety (Inpari 3 and Inpari 30 Ciherang Sub 1) as the second factor with four replications. There was no interaction between seedling age and rice variety for all parameters observed. Seedling age significantly affected total chlorophyll, plant height, number of grains per panicle, percentage of filled grain, and harvest yield. Furthermore, rice variety only affected plant height and harvest yield. Although 21 DAS resulted in higher plants, 14 DAS showed better physiological performance and productivity. Specifically, 14 DAS seedlings had higher total chlorophyll content, more grains per panicle, a greater percentage of filled grain, and higher harvest yield. The Inpari 3 rice variety produced lower plant growth and harvest yield than Inpari 30 Ciherang Sub 1 rice variety. In correlation analysis, total chlorophyll content caused an increase in the percentage of filled grain and harvest yield (r= 0.53 and r= 0. 28), while plant height caused a decrease in harvest yield (r= -0.30).